Virtual routers a tool for networking research and education. - Baumgartner, Florian (Computer communication review.)
Virtual routers are software entities, i.e. user space processes, emulating IP routers on one or several (Linux) computers. Virtual routers can be used for both networking research and education. In contrast to simulation, virtual routers process packets in real-time and the virtual router code is similar to code in real routers. In the case of research, larger network test-beds can be built using a relatively small number of computers. New functionalities such as new queuing mechanisms are supported by a modular software architecture and can be tested in a rather safe environment compared to kernel space implementations. Virtual routers can also be used as a tool aiming to allow students to perform virtual experiments within a computer networks course. Students can create and experiment with arbitrary virtual IP network topologies. The web-based user interface allows students to interact remotely with the emulated routers, but simultaneously it is very similar to commonly available configuration interfaces of network devices in reality. This enables students to configure routers like in the real world but also to experiment in a much more robust and safe environment.